STRATEGI PEMASARAN SYARI’AH DALAM MENINGKATKAN MINAT BELI KONSUMEN DI HOME INDUSTRI MAULANA BATIK SITUBONDO - Lusi Oktaviani; Zainul Anwar; Evi Nuril Latifah (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2024)
In the modernization era, many companies were founded, one of which was the Maulana Batik Situbondo Home Industry. In a business, of course the Maulana Batik Situbondo Home Industry has a marketing strategy to achieve the goals desired by consumers and customers. This research only focuses on two problems, namely how sharia marketing strategies increase consumer buying interest in the Maulana Batik Situbondo Home Industry. What are the inhibiting and supporting factors for sharia marketing strategies in increasing consumer buying interest in the Maulana Batik Situbondo Home Industry? This research method is qualitative research using two types of data sources, namely primary data and secondary data. The data collection techniques used to collect data are observation, interviews and documentation. The results of this research state that the Maulana Batik Situbondo Home Industry implements a marketing mix. Namely, the products being bought and sold are halal products, the prices applied are prices that are easily accessible to consumers, the promotions used have no elements of fraud, and the location is strategic in the center of Situbondo City. Apart from that, the Maulana Batik Situbondo Home Industry also applies Islamic marketing characteristics in its strategy, namely rabbaniyyah, ethical, realistic and humanistic values.